Gastrostomy tube placement is safe in advanced amyotrophic lateral sclerosis. (2nd January 2017) - Kak, Manisha; Issa, Naoum P.; Roos, Raymond P.; Sweitzer, Bobbie Jean; Gottlieb, Ori; Guralnick, Amy; White, Steven R.; Semrad, Carol E.; Soliven, Betty; Baroody, Joumana; Rezania, Kourosh
Abstract: Objectives: To evaluate the safety and effect on survival of insertion of a gastrostomy tube (G-tube) in patients with amyotrophic lateral sclerosis (ALS) who have upright forced vital capacity (uFVC) ≤ 50% predicted. Current guidelines, which are based on higher rates of post-procedure complications in ALS patients with advanced respiratory dysfunction, have led to a recommendation to perform G-tube insertion before the FVC drops to <50% predicted, even when the patient has no significant dysphagia. Methods: We assessed 41 ALS patients who received a G-tube, mostly by insertion of a percutaneous endoscopic gastrostomy (PEG) tube by a dedicated team that included a gastroenterologist and one of two anesthesiologists using Monitored Anesthesia Care with deep sedation, and 61 patients who did not receive a G-tube. uFVC was ≤50% predicted in 12 of 41 patients who received a G-tube and in 18 of 61 who did not. Results: The procedure was safe regardless of FVC status, with low rates of post-operative complications in both low and high FVC groups. There was no survival benefit for patients who received a G-tube when compared with those who did not. Discussion: PEG insertion is safe in ALS patients with significant respiratory muscle weakness when performed by a dedicated team, which suggests that the recommendation for G-tube placement should not be based on the patient's respiratory status.